K-Pop and Contemporary Cultural Diplomacy: The Influence of K-Pop Idol Neo Culture Technology (NCT) on Indonesia’s Cultural Diplomacy in the Digital Age - Astrid Risa Miranti Zulkarnain; Karisma Nurul Izzah Suharyono (Hasanuddin University, 2022)
Globalization has influenced the polarization of international relations activities, especially towards implementing cultural diplomacy. Referring to transnationalism theory, non-state actors have dominated international relations activities by using popular culture and social media as a means of international communication. The implication of the role of non-state actors from among K-Pop idol groups is no exception to spreading a country's local culture as a form of cultural diplomacy. Therefore, this article sees the implications of NCT's transnational activities as a K-Pop idol group influencing the strategy and implementation of Indonesia's cultural diplomacy in the digital era. By using qualitative research methods with library research techniques and observing activities using social media, this article analyzes the role of NCT in spreading Indonesian culture globally through three approaches to cultural diplomacy, according to Cynthia Schneider, namely values, audience, and environmental approaches. Through these three approaches, this article underlines that the role of NCT in spreading Indonesian cultural values has an impact on the formation of the basis of trust and the image of Indonesia internationally. Then the use of social media carried out by NCT has succeeded in expanding the target of Indonesian cultural diplomacy, which can be seen through the achievement of a considerable number of audiences and enhanced regional reach. In addition, the role of NCT in spreading Indonesian culture also influences the strategy and policy of Indonesia's cultural diplomacy. It is shown through the recognition and use of NCT in one of the Ministry of Creative Economy and Tourism projects. Thus, these article findings show the role of NCT in Indonesia's cultural diplomacy as a form of popular culture utilization, the K- Pop, and extend the effectiveness of using social media as a means of cross-country communication in the digital age.